Szachy między grą-zabawą, sportem a e-sportem = Chess: a game, a sport or an e-sport - Dąbrowski, Michał (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to determine how chess should be classified.Based on the literature review, three possible answers are proposed: chessis a sport, chess is a game and pastime, chess is an e-sport. The theoretical concepts were subjected to empirical verification. 18 individual in-depth interviews were conducted. The respondents were: active chess players,parents of competitive chess players, chess instructors, chess enthusiasts,e-sports and computer games fans, and people who were not interested in chess or e-sports.
Keywords: szachy; gra; zabawy; sport; e-sport; chess; games; e-sports; pastime